Potensi Pengurangan Emisi Gas Kabron dengan Perencanaan PLTS Atap pada Gedung Fakultas Teknik 03 Untidar - Muhammad Amrullah; Deria Pravitasari; Sapto Nisworo (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
One way to reduce carbon dioxide emissions from power plants powered by fossil fuels is by utilizing new renewable energy sources to generate the electrical energy needed each day. The Faculty of Engineering 03 UNTIDAR Building has a roof area of 997.4 m2 and a solar irradiation potential of 4.89 kWh/m2 per day, so it is very probable to build a rooftop PLTS to supply the building's lighting demand. Therefore, a plan for installing a rooftop PLTS system was implemented in this study in order to contribute to the utilization of new, renewable energy and the reduction of carbon dioxide emissions. The method employed in this planning is descriptive analysis, which includes analyses of the locations for installing solar modules, the building's daily electricity usage, the technical design of the rooftop PLTS system, analyses of the energy produced, and analyses of the potential to lower carbon dioxide emissions. According to the planning results, the rooftop PLTS has a capacity of 124 kWp and can generate 135,299,299.29 kWh of electrical energy annually utilizing 231 units of 540 W solar modules that are divided into 10 strings. 8,267.97 kWh are typically exported each month to PT. PLN as electrical energy. While the potential reduction in carbon dioxide emissions is calculated to be 135,299.29 tons of CO2 annually.